Does Competition within the Military Reduce Expropriation? - ANEY, Madhav S. (Institutional Knowledge at Singapore Management University, 2013)
How can agents in the military, which control the means of coercion, commit not to expropriate from producers? In this paper we propose competition within the military as one of the mechanisms that can deter predation and consequently create commitment. In our model, even if agents within the military could expropriate all output costlessly, it is attractive to protect producers from predating military units. This is because there is a marginal defensive advantage and consequently defense is an e ective way to potentially eliminate other military units, reducing competition and leading to higher future payo s. The model predicts that that greater internal competition within the military lowers the risk of expropriation. We find robust correlations in the data that suggest that the competition effect we model can explain short run fluctuations in the expropriation risk within countries for countries at lower stages of institutional and economic development. These results indicate that there may be a short run component to property rights institutions that varies with the degree competition among agents who control the means of coercion.